Teaching English pronunciation with the textbook English 11 at Dong Hy High School - Hoang, Thi Thanh Hoa (University of Languages and International Studies, 2017)
English language is considered as a main tool for global communication in the modern world and pronunciation is considered as the key to successful communication. Therefore, teaching pronunciation plays a very important role in language teaching. Being abl (...)